Water and Sanitation for the 21st Century: Health and Microbiological Aspects of Excreta and Wastewater Management (Global Wate 2019
DOI: 10.14321/waterpathogens.19
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Excreted and Waterborne Viruses

Abstract: The designations employed and the presentation of material throughout this publication do not imply the expression of any opinion whatsoever on the part of UNESCO concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The ideas and opinions expressed in this publication are those of the authors; they are not necessarily those of UNESCO and do not commit the Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
1
20
2
1
Order By: Relevance
“…Many enteric bacteria, protozoa, and some STH can be transmitted by animal feces [26]. Zoonotic transmission of enteric viruses are rare, with the exception of rotavirus and Hepatitis E [26,57]. Consistent with these pathways, we found that animal ownership was associated with higher odds of protozoal infection, and trended towards higher odds of bacterial and STH infection and lower odds of viral infection.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Many enteric bacteria, protozoa, and some STH can be transmitted by animal feces [26]. Zoonotic transmission of enteric viruses are rare, with the exception of rotavirus and Hepatitis E [26,57]. Consistent with these pathways, we found that animal ownership was associated with higher odds of protozoal infection, and trended towards higher odds of bacterial and STH infection and lower odds of viral infection.…”
Section: Discussionsupporting
confidence: 69%
“…At the taxa-level, we observed higher odds of infection among CU5 compared to other age groups only for protozoa, an association driven largely by Giardia, which is one of the first enteric pathogens to infect children [56], and the most common infection in our study population. We found no significant difference in odds of infection across age groups for half of the 18 pathogens in our species-specific analysis, including rotavirus, which is the leading cause of acute gastroenteritis in infants and young children in developing countries [57], the leading cause of death due to diarrhea among children <5 [58], and is typically considered a childhood illness [59]. One explanation for these associations is that intra-household transmission may be a key transmission pathway for enteropathogens.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Wastewater is a complex matrix that comprises a large variety of pathogenic and commensal viruses and provides important information about virus circulation, the introduction of emergent viruses and how they are transmitted among the population [ 1 ]. Waterborne viruses are generally nonenveloped and excreted in high numbers by infected individuals with or without disease, and in some cases long after the resolution of symptoms [ 2 ]. The study of excreted viruses is a very useful tool known as wastewater-based epidemiology, which has the potential to act as a complementary approach for current infectious disease surveillance systems and an early warning system for disease outbreaks [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After conducting an extensive revision on the most commonly used methods for concentrating viruses from wastewater samples in the last 2 years, Bofill-Mas and Rusiñol described that viral concentration methods had been mostly focused on combinations of flocculation/precipitation strategies [ 25 ]. Traditionally, viral environmental surveillance has considered principally RNA enteric viruses and also DNA viruses abundantly excreted in faeces, urine or skin desquamation as adenoviruses, polyomaviruses and papillomaviruses, which are all nonenveloped virus [ 2 ]. In fact, in 2015, Wigginton et al.…”
Section: Introductionmentioning
confidence: 99%